APOE Genotype Moderates the Relationship Between Plasma Phosphorylated‐tau181 and Pattern Separation Performance in Non‐demented Adults. (20th December 2022) - Diaz, Valentina E; Memel, Molly B; Gaynor, Leslie S; Gontrum, Eva Q.; Chan, Brandon; Lago, Argentina Lario; Yassa, Michael A.; Rojas, Julio C.; Casaletto, Kaitlin B; Kramer, Joel H.; Saloner, Rowan
Abstract: Background: The apolioprotein e (APOE) e4 allele enhances risk for Alzheimer's disease (AD), particularly an amnestic AD phenotype with medial temporal lobe tau pathology. Pattern separation, the ability to discern novel yet similar information from previously learned information, is a cognitive marker of hippocampal function. APOE e4 carriers often exhibit pattern separation deficits prior to conversion to AD dementia, however the impact of APOE on tau‐related pattern separation performance is unknown. We examined the relationship between plasma P‐tau181 and pattern separation performance in non‐demented adults, and tested whether this association was dependent on APOE e4 genotype. Methods: Plasma P‐tau181 levels were measured (Quanterix Simoa) in 171 non‐demented adults (139 cognitively unimpaired, 32 mild cognitive impairment; 29% APOE e4+, 54% female, aged 52‐92) who completed a validated behavioral task of visual pattern separation recognition. The lure discrimination index (LDI), reflecting ability to discriminate similar 'lure' items from old items, was modeled as the primary outcome. Linear regression examined LDI scores as a function of plasma P‐tau181, APOE4 genotype, and their interaction, controlling for age, sex, and education. Result: APOE e4+ had higher plasma P‐tau181 than e4‐ (Cohen's d=0.64, p<0.001), but APOE4 groups did not differ on LDI scores (Cohen's d=0.27, p=0.124). In the full sample, higher plasma P‐tau181 significantly related to lower (worse) LDI scores (β=‐0.17, p=0.028). APOE4 status significantly moderated the relationship between plasma P‐tau181 and LDI scores (β=‐0.29, p=0.030) such that higher P‐tau181 related to lower LDI scores in e4+ (β=‐0.38, p=0.004) but not in e4‐ individuals (β=‐0.02, p=0.824). Conclusions: APOE e4+ individuals had elevated plasma P‐tau181, which in turn related to worse pattern separation performance only within e4+ individuals. These data suggest that APOE4‐related elevations in plasma P‐tau181 may be particularly sensitive to hippocampal functioning outcomes prior to frank dementia, which could reflect underlying hippocampal hyperexcitability due to e4‐mediated GABAergic interneuron loss. Future work incorporating imaging markers of brain structure and function may help elucidate whether P‐tau181‐related alterations in pattern separation among e4+ individuals are mediated by hippocampal‐specific mechanisms.